Systematic Analysis of the Clinical Significance of Hyaluronan-Mediated Motility Receptor in Colorectal Cancer - Tang, Yan-ping; Yin, Yi-xin; Xie, Ming-zhi; Liang, Xin-qiang; Li, Ji-lin; Li, Ke-zhi; Hu, Bang-li (Frontiers in Molecular Biosciences, 2021)
Background: The role of hyaluronan mediated motility receptor (HMMR) in colorectal cancer (CRC) remained to be elucidated. The present study aimed to explore the association of HMMR with the development and prognosis of CRC using the sequence datasets, clinical tissues, blood samples and cell lines. Methods: The CRC datasets were downloaded from TCGA and GEO databases. Forty CRC tissues and 120 blood samples were collected. Four CRC cell lines (HCT116, HT-29, LoVo and SW480) and one normal cell line (NCM460) were cultured. RT-qPCR was used to determine the expression of HMMR in tissues and cell lines. ELISA assay was applied to measure the HMMR levels in blood samples. Results: Expression of HMMR was significantly increased in the CRC tissues compared with the corresponding adjacent tissues based on TCGA dataset, seven GEO datasets and the clinical CRC tissues. No associations were found between HMMR expression with TNM stage and other clinical parameters. Expression of HMMR in CRC cell lines varied among different cell lines. The blood levels of HMMR were slightly increased in CRC patients compared with healthy controls. The TCGA and GEO datasets showed inconstant results regarding the association of HMMR expression with the survival of CRC patients. Conclusions: HMMR was increased in CRC tissues but not in blood. Expression of HMMR was independent of CRC development, but has no prognostic significance in patients with CRC.